Pengetahuan, dan Kemampuan Finansial terhadap Minat Mahasiswa Berinvestasi di Saham Syariah dengan Risiko Investasi sebagai Variabel Intervening - Siti Baroroh Barid; Deny Yudiantoro (IPM2KPE, 2023)
This study aims to determine the effect of knowledge, financial ability, and investment risk on students' interest in investing in Islamic stocks, and to show the possibility of investment risk mediating the relationship between knowledge and financial ability and investment interest. This research method is quantitative. Data was taken from 87 student respondents. Data analysis was tested using the SPSS tool with multiple linear regression tests, and hypothesis testing. The results showed that the equation from the results of multiple linear analysis was Y = -3.949 + 0.186 X1 + 0.602 X2 + e. In conclusion, investment knowledge has no significant effect on student investment interest in Islamic stocks. Financial capability has a significant influence on students' interest in investing in Islamic stocks. Investment risk has no significant effect on students' interest in investing in Islamic stocks. Other factors such as family experience and risk-taking tendency in investing, have more influence on student decisions in investing. Keywords: Financial, Investment, Sharia